Alpha-Amylase Activity in Feline Saliva: An Analytical Validation of an Automated Assay for Its Measurement and a Pilot Study on Its Changes Following Acute Stress and Due to Urinary Tract Pathologies - Esmeralda Cañadas-Vidal; Alberto Muñoz-Prieto; Juan D. García-Martínez; Jose J. Ceron; Luis Pardo-Marín; Asta Tvarijonaviciute (Animals)
Salivary alpha-amylase (sAA) increases in response to stressful stimuli in a number of animal species, and it is considered a biomarker of sympathetic nervous system activation. However, no studies have been performed in which sAA has been measured in cats. The aim of this study was to perform an analytical and clinical validation of a commercially available automated assay for the determination of sAA in feline saliva. For the analytical validation, the precision, accuracy, and lower limit of quantification (LLOQ) were determined. To evaluate its response to acute stress, sAA was evaluated in feline saliva before and after stressful stimuli, consisting of a blood extraction. In addition, the sAA activity was compared between cats suffering from urinary tract pathologies and healthy controls. Analytical validation studies confirmed the method as being precise, accurate, and sufficiently sensitive for the sAA determination in cats. When the response to stress was evaluated, a statistically significant increase was detected in sAA in comparison with its activity before the blood extraction. In addition, cats with urinary tract diseases presented higher sAA activity than controls. The results of the present study indicate that sAA can be measured in feline saliva. This study could contribute to a wider use of the measurements of sAA in the saliva of cats and serve as a basis for future investigations aiming to assess acute stress in this species in a non-invasive manner.